PENGARUH MEDIA PEMBELAJARAN PAPAN PENGURANGAN BILANGAN CACAH (BILCA) TERHADAP HASIL BELAJAR SISWA KELAS III PADA PELAJARAN MATEMATIKA DI UPTD SDN PEJAGAN 1 BANGKALAN - Budiarti, Nyuransih Tri; Hariyani, Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
It is known that since the implementation of the Merdeka Curriculum, which is a new curriculum in the school environment, the level of student learning achievement is still relatively poor or low. This is indicated by the inconsistency of learning scores with the Minimum Completion Criteria (KKM) that has been set, which is 70. Based on data obtained from class III-B teachers, out of a total of 30 students, only 10 students were able to achieve scores above the KKM. Meanwhile, most students, namely 20 people, still obtained scores below the specified completion limit. This finding indicates that further evaluation is needed in the learning process and curriculum implementation so that student learning outcomes can be improved as much as possible. Based on observation experience during the School Field Introduction (PLP) 2 period in class III of UPTD_SDN Pejagan 1 Bangkalan, it is known that students understand better using learning media than just using a blackboard. The use of learning media is very minimal by teachers at UPTD SDN Pejagan 1 Bangkalan, especially in mathematics subjects due to the limited learning media in schools, making students find it difficult to understand the material on whole numbers, as seen from the way students respond when learning begins, they are more active in using learning media than just using a blackboard.This research aims to determine the effect of whole number subtraction board (BILCA) learning media on the learning outcomes of class III students in mathematics at UPTD SDN Pejagan 1 Bangkalan. Based on the output obtained sig 0.000 < 0.05 so it can be concluded that this shows that there is an average difference between research subjects and the whole number reduction board (BILCA) learning media on the learning outcomes of class III students. This is proven by the results of students' test questions regarding subtraction of whole numbers which were obtained based on the output that had been tested and obtained data descriptions that had a significant value of 0.000 < 0.05. So there is an influence of whole number subtraction board learning media on student learning outcomes in mathematics lessons in class III UPTD SDN Pejagan 1 Bangkalan.